Radiobiological Basis for Cancer Therapy by Total or Half-Body Irradiation - Kiyohiko Sakamoto (SAGE Publishing, 2004)
The tumor control effects by total-body irradiation (TBI) or half-body irradiation (HBI) on tumor-bearing mice and human cancer were investigated. In fundamental studies using a murine experimental system, mice that received 10 or 15 cGy of TBI showed a high value of TD 50 (number of tumor cells required for successful transplantation to a half group of injected sites) compared with nonirradiated control mice. The combination of low doses of TBI and local irradiation on tumor-bearing mice demonstrated enhanced tumor cell killing compared with only local irradiation, but this tumor-cell killing effect was not observed following 10 or 15 cGy of TBI alone. However, the suppression of distant metastasis of tumor cells was observed following low doses of TBI alone. Immunological studies on these effects suggested that TBI or HBI caused immunopotentiating effects. In clinical studies, malignant lymphoma (non-Hodgkin's lymphoma) was selected as the first disease for clinical trial. The results were promising for tumor control applications, except for advanced cases and very aged patients.